Asymptotic behavior of metric spaces at infinity - Bilet, V.V.; Dovgoshey, O.A. (Доповіді НАН України, 2017)
A new sequential approach to investigations of the structure of metric spaces at infinity is proposed. Criteria for the finiteness and boundedness of metric spaces at infinity are found.